STUDI PERBANDINGAN PERSEPSI TINGKAT TOLERANSI ANTARA MAHASISWA ASAL PAPUA DAN MAHASISWA LUAR NON-PAPUA (SUMATERA NON-RIAU) DI UNIVERSITAS RIAU - Fania Zhapira; Hambali Hambali; Ahmad Eddison (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This research is motivated by the increasing number of cases of intolerance towards certain ethnicities, especially in the campus environment. The case of intolerance that is still warm in memory is the case of the student siege of Papuan students in Surabaya. The formulation of the problem in this study is whether there is a difference in the perception of the tolerance level of students at the University of Riau between the perspectives of students from Papua and the perspectives of non-Papuan students (Non-Riau Sumatra) at the University of Riau. The purpose of this study was to determine whether there were differences in the perception of the tolerance level of students at the University of Riau between the perspectives of students from Papua and the perspectives of non-Papuan students (Sumateranon-Riau) at the University of Riau. This research is quantitative through statistical analysis method with Independent Sample T-Test with the help of SPSS. This study uses data collection techniques through observation, questionnaires and Library Research. To take the sample, this study used purposive sampling technique with a sample of 26 people, namely 13 students from Papua and 13 students from non-Papuans (non-Riau Sumatra). Based on the results of the study, it can be seen that the perception of the tolerance level of students at the University of Riau according to the perspective of students from Papua at the University of Riau is 69.87% "High". Meanwhile, the perception of the tolerance level of students at the University of Riau according to the perspective of non-Papuan foreign students (Non-Papuan Sumatra) at the University of Riau is 76.72% "Very High". Based on the results of the processed research data, the results obtained Sig. (2-tailed)> 0.05, namely 0.382 and 0.383. This means that there is no significant difference between the perception of the tolerance level of students at the University of Riau between the perspectives of students from Papua and the perspectives of non-Papuan students (Non-Riau Sumatra) at the University of Riau. Thus, the formulation of the hypothesis (Ha) is rejected while the formulation of the hypothesis (H0) is accepted.Key Words: Comparative Studies, Perceptions, Tolerance Levels, Papuan Students, Non- Papuan Foreign Students